Study of carbon dioxide-methane reaction using Co- and Ca- promoted MnO/gamma-Al2O3 catalysts - Saidina Amin, Nor Aishah; Hii, King Kui; Istadi, Istadi (2003)
The performance of Co-MnO/gamma-Al2O3 and Ca-MnO/gamma-Al2O3 catalysts in the carbon dioxide-methane reaction to produce syngas and C2-hydrocarbons has been reported. The most promising Ca- and Co-containing catalyst were characterized by using X-ray Diffraction (XRD), Nitrogen Adsorption (NA) ans Scanning Electron Microscopy (SEM). The catalysts were tested in a fixed-bed quartz reactor at atmospheric pressure, 800C and methane to carbon dioxide ratio of unity for five hours. The 5 wt.% Ca-12 wt.% MnO/gamma-Al2O3 catalyst was found to be the most stable against coking while 5 wt.% Co-12 wt.% MnO/gamma-Al2O3 was more suitable to produce syngas (H2 and CO). Both catalysts showed low activities toward C2 formation.